Objective Comparison of the First-Person–View Live Streaming Method Versus Face-to-Face Teaching Method in Improving Wound Suturing Skills for Skin Closure in Surgical Clerkship Students: Randomized Controlled Trial - Freda Halim; Allen Widysanto; Petra Octavian Perdana Wahjoepramono; Valeska Siulinda Candrawinata; Andi Setiawan Budihardja; Andry Irawan; Taufik Sudirman; Natalia Christina; Heru Sutanto Koerniawan; Jephtah Furano Lumban Tobing; Veli Sungono; Mona Marlina; et al. (JMIR Medical Education)
Abstract BackgroundThe use of digital online teaching media in improving the surgical skills of medical students is indispensable, yet it is still not widely explored objectively. The first-person–view online teaching method may be more effective as it provides more realism to surgical clerkship students in achieving basic surgical skills. ObjectiveThis study aims to objectively assess the effectiveness of the first-person–view live streaming (LS) method using a GoPro camera compared to the standard face-to-face (FTF) teaching method in improving simple wound suturing skills in surgical clerkship students. MethodsA prospective, parallel, nonblinded, single-center, randomized controlled trial was performed. Between January and April 2023, clerkship students of the Department of Surgery, Pelita Harapan University, were randomly selected and recruited into either the LS or FTF teaching method for simple interrupted suturing skills. All the participants were assessed objectively before and 1 week after training, using the direct observational procedural skills (DOPS) method. DOPS results and poststudy questionnaires were analyzed. ResultsA total of 74 students were included in this study, with 37 (50%) participants in each group. Paired analysis of each participant’s pre-experiment and postexperiment DOPS scores revealed that the LS method’s outcome is comparable to the FTF method’s outcome (LS: mean 27.5, SD 20.6 vs FTF: mean 24.4, SD 16.7; P ConclusionsFirst-person–view LS training sessions could enhance students’ ability to master simple procedural skills such as simple wound suturing and has comparable results to the current FTF teaching method. Teaching a practical skill using the LS method also gives more confidence for the participants to perform the procedure independently. Other advantages of the LS method, such as the ability to study from outside the sterile environment, are also promising. We recommend improvements in the audiovisual quality of the camera and a stable internet connection before performing the LS teaching method.